2018
DOI: 10.1136/bmjsrh-2017-101798
|View full text |Cite
|
Sign up to set email alerts
|

“I think maybe 10 years seems a bit long.” Beliefs and attitudes of women who had never used intrauterine contraception

Abstract: Aim: To explore, in general practice settings the concerns, beliefs and attitudes about intrauterine contraception reported by women, who had never used the methods.Method: We used a sequential mixed-method (QUAL/quant) approach. A pragmatic, self-selecting sample of thirty women, aged 18-46 years, who had never used intrauterine contraception (IUC), was recruited through seven general practices in South East England. Themes arising from qualitative interviews were used to construct a quantitative survey, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The effect of this is likely to be unnecessary restriction in recommending IUC for women for whom it is a valid and safe contraceptive option. Our study of the views of never-users of IUC, reported in another article that appears in this journal , suggests a double barrier effect: IUC is not offered to women because they do not request it, but women do not have good knowledge of IUC, and opportunities to discuss the method are being missed 17. This impasse is reinforced by the barriers identified around training, which is not seen as a priority when low demand does not justify its time and expense.…”
Section: Discussionmentioning
confidence: 80%
“…The effect of this is likely to be unnecessary restriction in recommending IUC for women for whom it is a valid and safe contraceptive option. Our study of the views of never-users of IUC, reported in another article that appears in this journal , suggests a double barrier effect: IUC is not offered to women because they do not request it, but women do not have good knowledge of IUC, and opportunities to discuss the method are being missed 17. This impasse is reinforced by the barriers identified around training, which is not seen as a priority when low demand does not justify its time and expense.…”
Section: Discussionmentioning
confidence: 80%
“…Seven included studies were conducted in the USA 28–34. The remaining studies were conducted in Australia (n=3),35–37 New Zealand (n=2),38 39 UK (n=2),40 41 France (n=1)42 and the Ireland (n=1) 43. Eight studies focused on the views of HCPs, six on contraceptive users and two on both groups.…”
Section: Resultsmentioning
confidence: 99%
“…Of the eight studies which included users or members of the public, one study purposively recruited women from African American groups,28 four papers included detailed ethnicity of participants29 31 32 41 and three studies had no mention of ethnicity 35 42 43. The papers that did not include ethnicity did mention purposive sampling for socioeconomic groups or various urban/rural locations 35 42 43.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations